An apple sucrose transporter MdSUT2.2 is a phosphorylation target for protein kinase MdCIPK22 in response to drought. Issue 3 (2nd October 2018) - Ma, Qi‐Jun; Sun, Mei‐Hong; Lu, Jing; Kang, Hui; You, Chun‐Xiang; Hao, Yu‐Jin
Summary: Sugars increase with drought stress in plants and accumulate in the vacuole. However, the exact molecular mechanism underlying this process is not clear yet. In this study, protein interaction and phosphorylation experiments were conducted for sucrose transporter and CIPK kinase in apple. The specific phosphorylation site of sucrose transporter was identified with mass spectrometry. Transgenic analyses were performed to characterize their biological function. It was found that overexpression of sucrose transporter gene MdSUT2.2 in apple plants promoted sugar accumulation and drought tolerance. MdSUT2.2 protein was phosphorylated at Ser 381 site in response to drought. A DUALmembrane system using MdSUT2.2 as bait through an apple cDNA library got a protein kinase MdCIPK22. Bimolecular fluorescence complementary (BiFC), pull‐down and co‐immunoprecipitation (Co‐IP) assays further demonstrated that MdCIPK22 interacted with MdSUT2.2. A series of transgenic analysis showed that MdCIPK22 was required for the drought‐induced phosphylation at Ser 381 site of MdSUT2.2 protein, and that it enhanced the stability and transport activity of MdSUT2.2 protein. Finally, it was found that MdCIPK22 overexpression promoted sugar accumulation and improved drought tolerance in an MdSUT2.2‐dependent manner in transgenic apple plants. MdCIPK22‐MdSUT2.2 regulatory module shed light on the molecular mechanism by which plant accumulates sugars and enhances tolerance in response to drought stress.